Effect of defibrotide on platelet function - (:unkn) unknown (THIEME MEDICAL PUBL INC, 1996)
Defibrotide, a polydeoxyribonucleotide, has been found to modulate endothelial cell function, causing an increase in tissue plasminogen activator (t-PA) levels, a decrease in plasminogen activator inhibitor (PAI) levels, and an increase in prostaglandin I-2 (PGI(2)) formation in humans. Defibrotide has no direct anticoagulant effect but has a synergistic action with heparin. A strong antithrombotic effect has been observed in animal models. Thus, defibrotide has a beneficial effect in cases of deep venous thrombosis (DVT), peripheral obliterative vascular disorder (POVD), stroke, vasculitis, and thromboembolism. Defibrotide also inhibits platelet function and activation. A significant decrease in platelet aggregate formation on the suture line in microarterial anastomosis in rats is one way defibrotide can inhibit platelet function and activation. In humans, a slight prolongation of the lag period in collagen-induced aggregation has been observed. In addition, a slight decrease in the maximum amplitude of the secondary wave of ADP and adrenalin-induced aggregations was also found. Platelet adhesion is diminished, the platelet differential count on formvar membrane is altered, and platelet aggregate formation is significantly inhibited. With an increase in platelet cyclic AMP (cAMP) content and a decrease in malonyl dialdehyde (MDA) and thromboxane B-2 (TXB(2)) formation, the levels of platelet secretion products such as PF-4 and beta-thromboglobulin (beta-TG) in plasma decreased progressively. It was also demonstrated that the C-14-glucose transport defect of the platelet membrane of atherosclerotic patients was partially corrected with defibrotide treatment.
Keywords: defibrotide; platelets; platelet adhesion; membrane transport; platelet gamma glutamyl transferase; THROMBUS FORMATION; ATHEROSCLEROSIS; TRANSPORT; GLUCOSE; DOGS